The possibilities of personnel development principle adaptability in personnel training - Stankevičienė, Asta; Liučvaitienė, Aušra; Volungevičienė, Diana (Business: Theory and Practice, 2008)
The article analyzes the conception of personnel training in accordance with the publications of Lithuanian and foreign authors. Therewith the survey was carried out to investigate the possibilities of applying the principle of personnel training in Lithuanian enterprises. This survey was carried out using the expert questioning of top managers and it provides the possibility of assessing the situation and problems of personnel training. Finally, the ways how to apply personnel training in Lithuanian enterprises are discussed in the article.Article in Lithuanian.Ugdymo principo taikymo galimybės personalui mokytiSantrauka. Straipsnyje, remiantis Lietuvos ir užsienio autorių publikacijomis, pagrįsta personalo ugdymo koncepcija. Atliktas personalo ugdymo principo taikymo galimybių Lietuvos įmonių personalui mokyti tyrimas, naudojant ekspertinę įmonių vadovų  apklausą,  leido  įvertinti  ugdymo  būklę  ir  problemas.  Aptartos  taikytinos personalo  ugdymo  priemonės  Lietuvos  įmonėms.Reikšminiai žodžiai: personalo ugdymas, personalo ugdymo koncepcija, personalo ugdymo procesas, personalo ugdymo priemonės.First published online: 19 Sep 2008